Biomass and low-density polyethylene waste composites gasification: Orthogonal array design of Taguchi technique for analysis and optimization. (5th August 2022) - Hasanzadeh, Rezgar; Mojaver, Parisa; Chitsaz, Ata; Mojaver, Mehran; Jalili, Mohammad; Rosen, Marc A.
Abstract: This modeling study explores and optimizes the performance of the gasification of a rice husk and low-density polyethylene waste composite utilizing an orthogonal array design of a Taguchi technique. This modeling study uses a signal to noise ratio analysis to optimize the gasification of rice husk and low-density polyethylene waste composite and utilizes an analysis of variance approach to identify the most important factors contributing to the process. It is shown that the composition ratio of rice husk and polyethylene waste contributes significantly to the gasification performance. Increasing composition ratio of rice husk and polyethylene waste improves hydrogen concentration, decreases carbon dioxide concentration and enhances carbon monoxide concentration. Energy efficiency is enhanced and normalized carbon dioxide emission is improved by increasing composition ratio of rice husk and polyethylene waste. The gasification of rice husk and low-density polyethylene waste composite is efficient (total energy efficiency of 77.6%) and clean (normalized carbon dioxide emission of 2.1 g/mol, based on the composite entering the system) at its multi-objective optimum conditions. The research results support the development of a system for gasification of biomass and plastic waste composites utilizing orthogonal array design of a Taguchi approach. Highlights: Rice husk and low-density polyethylene waste composites gasification was developed. Taguchi technique was utilized for analysis and optimization. Biomass/plastic waste composition ratio markedly affects gasification performance. Total energy efficiency of 77.6% was achieved. Normalized carbon dioxide emission was obtained by 2.1 g/mol.